1972
DOI: 10.1203/00006450-197205000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated to Dr. Guido Fanconi on the occasion of his 80th birthday Catch-up Growth in Malnutrition, Studied in Celiac Disease After Institution of Gluten-free Diet

Abstract: ExtractCeliac disease provides a model for investigation of one form of infantile malnutrition occurring under fully controlled circumstances. Thirteen patients aged 9-15 months were followed for a period of at least 3 years while they were on a strict gluten-free diet.Observed values for height, weight, bone age, metacarpal diameter, and cortical thickness are compared with the normal range based on local standards, and the results are expressed as standard scores. The mean curves of these data are presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

1975
1975
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 23 publications
4
32
0
1
Order By: Relevance
“…Withdrawal of gluten from the diet constitutes removal of the pathogenetic factor and is an effective treatment for CCD. After institution of a gluten-free diet, the symptoms usually disappear quite rapidly and most patients exhibit complete catch-up growth [5, 6, 7]. These characteristics render CCD an elegant human model for the study of catch-up growth.…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawal of gluten from the diet constitutes removal of the pathogenetic factor and is an effective treatment for CCD. After institution of a gluten-free diet, the symptoms usually disappear quite rapidly and most patients exhibit complete catch-up growth [5, 6, 7]. These characteristics render CCD an elegant human model for the study of catch-up growth.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional rehabilitation leads to growth acceleration in most CD patients. [8][9][10] GFD heals in fact the intestinal mucosa and corrects malabsorption, with a more rapid recovery of fat mass. 11,12 Results of our study was similar with a study by Cheng et al, which also showed a positive effect of a GFD by demonstrating weight gain in previously underweight patients and weight loss in those previously overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Esse fato pode ser explicado pelas próprias transgressões alimentares, que causam comprometimento da estatura nos indivíduos. Para a recuperação de deficit de estatura, é necessário um período maior do que o necessário para a normalização de peso: 2 a 3 anos, em média, contra 10 a 12 meses após o início do tratamento dietético, respectivamente 38,40,41 . No critério de inclusão deste estudo, definiu-se que o diagnóstico de doença celíaca e a prescrição de dieta sem glúten tivessem sido realizados há pelo menos um ano, com a expectativa de que esse período fosse suficiente para a completa recuperação ponderal e, ao menos, recuperação parcial de estatura.…”
Section: Carboidratounclassified